Question 30
If sec θ + tan θ = p, then find the value of cosec θ
Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class
CBSE Class 10 Sample Paper for 2019 Boards
Question 1
Question 2 (Or 1st)
Question 2 (Or 2nd) Important
Question 3 (Or 1st) Important
Question 3 (Or 2nd)
Question 4
Question 5 Important
Question 6 Important
Question 7 (Or 1st)
Question 7 (Or 2nd) Important
Question 8 (Or 1st)
Question 8 (Or 2nd)
Question 9
Question 10 Important
Question 11 Important
Question 12 Important
Question 13 Important
Question 14
Question 15
Question 16 (Or 1st) Important
Question 16 (Or 2nd)
Question 17 (Or 1st) Important
Question 17 (Or 2nd)
Question 18 Important
Question 19 (Or 1st)
Question 19 (Or 2nd) Important
Question 20
Question 21 (Or 1st) Important
Question 21 (Or 2nd)
Question 22
Question 23 (Or 1st) Important
Question 23 (Or 2nd)
Question 24
Question 25
Question 26
Question 27 (Or 1st)
Question 27 (Or 2nd) Important
Question 28 (Or 1st)
Question 28 (Or 2nd) Important
Question 29
Question 30 Important You are here
CBSE Class 10 Sample Paper for 2019 Boards
Last updated at May 29, 2023 by Teachoo
Question 30
If sec θ + tan θ = p, then find the value of cosec θ
Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class
Question 30 If sec θ + tan θ = p, then find the value of cosec θ Given sec θ + tan θ = p Converting sec θ and tan θ in sin θ and cos θ 1/cos𝜃 + sin𝜃/cos𝜃 = p (1 + sin𝜃)/cos𝜃 = p We need to find cosec θ, To find cosec θ , we convert everything into sin θ So, we square both sides ((1 + sin𝜃)/cos𝜃 )^2 = p2 (1^2 + sin^2𝜃 + 2 sin𝜃)/cos^2𝜃 = p2 1 + sin2 θ + 2 sin θ = p2 × cos2 θ Now, sin2 θ + cos2 θ = 1 cos2 θ = 1 – sin2 θ 1 + sin2 θ + 2 sin θ = p2 × (1 – sin2 θ) 1 + sin2 θ + 2 sin θ = p2 – p2 sin2 θ Let x = sin θ 1 + x2 + 2x = p2 – p2 x2 x2 + p2 x2 + 2x + 1 – p2 = 0 (1 + p2) x2 + 2x + (1 – p2) = 0 Comparing with ax2 + bx + c a = (1 + p2) , b = 2, c = (1 – p2) Now, x = (−𝑏 ± √(𝑏^2 − 4𝑎𝑐))/2𝑎 x = (−2 ± √(2^2 − 4 × (1 + 𝑝^2 ) × (1 − 𝑝^2 ) ))/2(1 + 𝑝^2 ) x = (−2 ± √(4 − 4 × (1 + 𝑝^2 ) × (1 − 𝑝^2 ) ))/2(1 + 𝑝^2 ) x = (−2 ± √4 √(1 − (1 + 𝑝^2 ) × (1 − 𝑝^2 ) ))/2(1 + 𝑝^2 ) x = (−2 ± 2 √(1 − (1 + 𝑝^2 ) × (1 − 𝑝^2 ) ))/2(1 + 𝑝^2 ) x = (−1 ± √(1 − (1 + 𝑝^2 ) × (1 − 𝑝^2 ) ))/((1 + 𝑝^2 ) ) x = (−1 ± √(1 − (1^2 −(𝑝^2 )^2 ) ))/((1 + 𝑝^2 ) ) x = (−1 ± √(1 − (1 − 𝑝^4 ) ))/((1 + 𝑝^2 ) ) x = (−1 ± √(1 − 1 + 𝑝^4 ))/((1 + 𝑝^2 ) ) x = (−1 ± √(𝑝^4 ))/((1 + 𝑝^2 ) ) x = (−1 ± 𝑝^2)/((1 + 𝑝^2 ) ) Putting x = sin θ sin θ = (−1 ± 𝑝^2)/((1 + 𝑝^2 ) ) For + sin θ = (−1 + 𝑝^2)/((1 + 𝑝^2 ) ) sin θ = (𝑝^2 − 1)/(𝑝^2 + 1) Therefore, cosec θ = 1/sin𝜃 = (𝒑^𝟐 + 𝟏)/(𝒑^𝟐 − 𝟏) For – sin θ = (−1 − 𝑝^2)/((1 + 𝑝^2 ) ) sin θ = (−(1 + 𝑝^2))/((1 + 𝑝^2 ) ) sin θ = –1 Therefore, cosec θ = 1/sin𝜃 = 1/(−1) = –1